PENYEBAB DAN PENANGANAN PLAGIARISME DI KALANGAN MAHASISWA PENDIDIKAN MATEMATIKA - Tiara Kusuma Astuti; Itoh Nur Sari; Karniasih Ramadhani; Syifa Restania Putri; Zulkardi Zulkardi; Novita Sari (Departemen Sastra Indonesia, Fakultas Sastra, Universitas Negeri Malang (UM), 2021)
This study aims to know the cause and prevent plagiarism for mathematics education students. The method in this study isqualitative with a literature study analysis technique approach. This study shows thatthe causes of plagiarism are the low self-confidence in writing works with their own thoughts, bad habits in learning, and think that doesn’t lead to learning process.